Oxidative stress increases MICA and MICB gene expression in the human colon carcinoma cell line (CaCo-2) - Yamamoto, Kazuo; Fujiyama, Yoshihide; Andoh, Akira; Bamba, Tadao; Okabe, Hidetoshi (Biochimica et biophysica acta, 2001)
The human major histocompatibility complex class I chain-related A gene (MICA) and the MICB gene are newly identified members of the major histocompatibility complex class I chain-related gene family. We demonstrate here that oxidative stress, induced by H 2O 2, promoted MICA (2.2-fold) and MICB (3.8-fold) gene expression using the human colon carcinoma cell line (CaCo-2) and semi-quantitative RT-PCR.